The association of maternal age, body mass index, physical activity with Gestational Diabetes Mellitus - Hazrat, Hina; Ahmed , Sadaf; Noushad , Shamoon (International Journal of Endorsing Health Science Research, 2018)
Background: Gestational diabetes mellitus (GDM) represents the state of carbohydrate intolerance during gestation. GDM is found as a risk factor for adverse outcomes of gestation concerning maternal and fetal health conditions. Increasing maternal age is found associated with GDM and also other obstetric complications. High maternal weight is reported to be linked to elevated risk of GDM. Relation of increased maternal age and elevated body mass index (BMI) state with GDM suggests a need of effective measures for improving the maternal and fetal health conditions and alienate the GDM associated obstetric concerns. Previous studies have found possible role of physical activity and exercise in reducing the risk of GDM development. This study aimed to explore GDM prevalence among participants and to perform comparative analysis of maternal age and BMI between participants without GDM and participants with GDM. Methodology: This cross-sectional study was conducted from March 2014 to September 2014, participants (n=133) filled in a questionnaire which aimed to assess parameters like age, BMI and physical activity for the study. Women in gestation were randomly invited to participate in study, and informed signed consent was obtained from each participant prior participation. Participants were categorized in two groups, participants without GDM and with GDM. For each participant, maternal age, BMI and involvement in physical activities were recorded. Data were analysed using IBM SPSS Statistics 24. Results: Mean values of maternal age and BMI were found to be lower for participants without GDM as compared to that of participants with GDM. Participants without GDM reported to be involved in household activities, occupational activities and exercise whereas participants with GDM were found to be only involved in household activities. Conclusion: In conclusion, this study may suggest possible influence of maternal age in GDM. Moreover, in view of findings which indicated higher mean value of maternal BM of participants with GDM compared to that of participants without GDM, and in view of physical activity state, weight measurement and healthy lifestyle may be encouraged.